Compensation of high nitrogen toxicity and nitrogen deficiency with biochar amendment through enhancement of soil fertility and nitrogen use efficiency promoted rice growth and yield. Issue 11 (18th September 2021) - Khan, Zaid; Nauman Khan, Mohammad; Luo, Tao; Zhang, Kangkang; Zhu, Kunmiao; Rana, Muhammad Shoaib; Hu, Liyong; Jiang, Yang
Abstract: The quality and nutritional status of agricultural soils are depleting gradually, and biochar is widely used in soil quality improvement. A sustainable approach of biochar application needs a better understanding of its interaction with nitrogen application and the final effect on crop growth. In our study, the effect of different biochar application levels (0, 15, 30, and 60 tons ha −1 ) in combination with nitrogen fertilizer levels (0, 150, 300, and 450 kg ha −1 ) on soil properties, rice growth, and nitrogen use efficiency were investigated. The results showed that sole application of biochar (B60) did not promote the rice growth except the soil organic carbon (SOC), total nitrogen, total phosphorous, and available potassium compared with no biochar addition, while a single application of 450 kg N ha −1 (N450) adversely affected the rice physiological and yield traits by destroying rice leaf ultrastructure and reducing the stomatal length by 13%, stomatal width 3% and density 12%, plant height 5%, dry biomass plant −1 4%, spike weight plant −1 8%, and grain weight plant −1 9% compared to N300 unless it was treated in combination with biochar. Biochar can significantly compensate the toxicity of excessive nitrogen and deficiency of low nitrogen fertilizer on rice growth. Compared to a single application of B0+N450 (450 kg N ha −1 ), combined application of biochar and nitrogen B30+N450 could elevate rice plant nitrogen content by 13%, plant height 30%, aboveground dry biomass plant −1 136%, spike weight plant −1 34%, and grain weight plant −1 36% while increments in total nitrogen accumulation (TNA 79%%) and nitrogen use efficiency (NUE 35%) were noted in B30+N300 treatment. These results suggest that biochar amendment combined with a proper amount of nitrogen fertilizer is an effective approach to promote soil conditions, manage nitrogen utilization, improve plant growth and increase crop yield on a sustainable basis. Abstract : A sustainable approach of biochar application needs a better understanding of its interaction with nitrogen application and the final effect on crop growth. Compared to a single application of B0+N450 (450 kg N ha −1 ), combined application of biochar and nitrogen B30+N450 could elevate rice plant nitrogen content by 13%; plant height, 30%; aboveground dry biomass plant, 1 136%; spike weight plant −1, 136%; and grain weight plant −1, 36%. These results suggest that biochar amendment combined with a proper amount of nitrogen fertilizer is an effective approach to manage nitrogen utilization, improve plant growth, and increase crop yield on a sustainable basis.